The Organizational Development at the kindergartens directors (Journal of the College of Basic Education, 2023)
The objective of the current research is to identify organizational development among kindergarten directors. The sample of the research includes 175 directors from the directorate of Kindergartens in Baghdad / alRusafa/1 – al-Rusafa/2 – al-Rusafa/3 and al-karkh/1/2/3 . To achieve the goals of the research , The researcher has adopted organizational development scale (word 2015) and this scale consists of 27 items distributed on five fields which are (strategic (6) items, Structural (6) items, Executive ( 5) items – Human resources management (5) items , technological ( 5) items. The researcher has verified apparent reliability and construction reliability. Scale of organizational development have been extracted by the method of the Vakronbach equation , and the researcher reached the following results: --The directors in kindergartens have organizational development.There are no differences between organizational development among kindergarten directors according to the educational qualification.There are differences between organizational development among kindergarten directors, according to years of service.